Innovation of Jamu Beras Kencur into a Healthy Processed Food Product: Custard Pudding - Setya Jayanti, Anggun; Hermawan, Budi; Ariani, Angela; Ade Septemuryanto, Syaiful (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2025)
This research is an experimental study entitled “Innovation of Jamu Beras Kencur into a Healthy Processed Food Product: Custard Pudding.” It is motivated by the declining interest of the younger generation in consuming jamu, which is one of Indonesia’s traditional beverages rich in health benefits. This situation led to the idea of innovating jamu into a European-style dessert, namely custard pudding. Custard pudding was chosen because it is highly favoured by the public. However, due to its milk content which can cause allergies, some people are unable to consume it. This study aims to explore the process of transforming jamu beras kencur into a custard pudding product. In addition, this research seeks to increase the interest of the younger generation in enjoying jamu in order to preserve Indonesian cultural heritage. This experiment employed purposive sampling as the data collection technique. The research instruments consisted of questionnaires and interviews distributed to 30 respondents. The data analysis techniques used were organoleptic tests and hedonic tests, followed by calculating the mean scores to determine the evaluation results based on predetermined aspects. The findings of the study, after conducting experiments and collecting data, revealed that the average organoleptic test scores for beras kencur custard pudding were 3.5 for taste, 3.3 for aroma, 3.3 for color, and 3.7 for texture. Meanwhile, the hedonic test resulted in an average score of 3.4. It can be concluded that the innovation of jamu beras kencur into a healthy food product in the form of custard pudding is acceptable to the public.